Fluidic device for electrophoresis of molecules - Lamagna, Alberto; Pérez, Maximiliano Sebastián|Lerner, Betiana; Berli, Claudio; Ordóñez, Andrés Felipe; Boselli, Alfredo; Sacco, Francisco; Salmoral, Elda María; Kreiner, Andrés Juan; Rinaldi, Carlos Alberto; Lasorza, Carlos (2012)
Fil: Lamagna, Alberto. Comisión Nacional de Energía Atómica; Argentina.